Evaluating intracellular redox status in L02 cells on microchip - Xu,Chunxiu (2013)
A novel microfluidic device integrated with continuous introduction of individual cells and detection of intracellular reducing species by laser induced fluorescence (LIF) detector is reported. A single channel with one sheath-flow channel located on each side of the sampling channel was designed. The intracellular reducing species were derivatized by a newly synthesized 2,2,6,6-tetramethyl-piperidine-1-oxyl (TEMPO)-based fluorescent probe. The labeled cells were hydrodynamically focused by sheath-flow streams and sequentially introduced into the sampling channel under hydrostatic pressure generated by adjusting liquid levels in the reservoirs. Intracellular reducing level in intact living L02 cells was detected by LIF without cytolysis. Upon stimulation with 100 µmol L-1 hydrogen peroxide for 30 min, the intracellular reducing level decreased in response to oxidative stress. A throughput of 41-44 cells min-1 was obtained.